2005
DOI: 10.1016/j.devcel.2005.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Factors Required for Microtubule Growth and Nucleation in the Early C. elegans Embryo

Abstract: Microtubules (MTs) are dynamic polymers that undergo cell cycle and position-sensitive regulation of polymerization and depolymerization. Although many different factors that regulate MT dynamics have been described, to date there has been no systematic analysis of genes required for MT dynamics in a single system. Here, we use a transgenic EB1::GFP strain, which labels the growing plus ends of MTs, to analyze the growth rate, nucleation rate, and distribution of growing MTs in the Caenorhabditis elegans embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
292
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(323 citation statements)
references
References 72 publications
28
292
2
1
Order By: Relevance
“…The large increase in astral MTs seen after knockdown of MCAK is consistent with earlier studies showing that MCAK and its orthologues have a dramatic effect on astral MT organization (Walczak et al, 1996;Grill et al, 2001;Maney et al, 2001;Kline-Smith and Walczak, 2002;Goshima and Vale, 2003;Rogers et al, 2004;Srayko et al, 2005). Unfortunately, we were unable to obtain FRAP recovery data on the astral MTs because of the difficulty in obtaining sufficient fluorescence signal to get reliable FRAP curves.…”
Section: What Is the Relationship Between Spindle Mt Dynamics And Orgsupporting
confidence: 88%
“…The large increase in astral MTs seen after knockdown of MCAK is consistent with earlier studies showing that MCAK and its orthologues have a dramatic effect on astral MT organization (Walczak et al, 1996;Grill et al, 2001;Maney et al, 2001;Kline-Smith and Walczak, 2002;Goshima and Vale, 2003;Rogers et al, 2004;Srayko et al, 2005). Unfortunately, we were unable to obtain FRAP recovery data on the astral MTs because of the difficulty in obtaining sufficient fluorescence signal to get reliable FRAP curves.…”
Section: What Is the Relationship Between Spindle Mt Dynamics And Orgsupporting
confidence: 88%
“…Although these two types of MTs differ in their global organization and function, they share three properties: (i) their nucleation requires the g-tubulin ring complex (known as g-TuRC) (Bartolini and Gundersen, 2006;Keating and Borisy, 1999;Mogensen et al, 2000;Petry and Vale, 2015); (ii) once nucleated, their minus-ends require protein complexes to cap and anchor them (Akhmanova and Hoogenraad, 2015); and (iii) they harbor dynamic properties, in part conferred by plus-end targeting proteins (Akhmanova and Steinmetz, 2015). Of note, although RNAi-mediated depletion of g-tubulin in C. elegans embryos reduces by 60% the level of MTs compared to wild-type embryos (Srayko et al 2005, O'Toole et al 2012, no bona fide g-tubulinindependent-microtubule nucleation pathway has thus far been reported (Petry and Vale, 2015).…”
Section: A C-tubulin Switch For the Generation Of Noncentrosomal Micrmentioning
confidence: 99%
“…Originally described in the zygote as a proxy for MT polymerization (Srayko et al, 2005), the plus-end binding protein EBP-2 has been observed is several epithelia, among which the epidermis (Green et al, 2011;Quintin et al, 2016;Wang et al, 2015) and the intestine .…”
Section: Plus-end Interacting Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another example, Srayko et al [77] built on data accumulated in previous RNAi studies to select a candidate list of genes that were known to influence microtubule-associated processes and might, therefore, function in microtubule nucleation or growth. They developed a sensitive visual assay based on distribution of an EBP-2::GFP transgenic marker that normally labels the growing (plus) end of microtubules.…”
Section: Candidate Gene Setsmentioning
confidence: 99%